Answer:
-2
Step-by-step explanation:
7−5+3−1
using BODMAS
A is addition and it comes before subtraction
7−(5+3)−1
7-8-1
then solve
7 - 9 = -2
Answer:
x=-1/7
Step-by-step explanation:
![\frac{3x-1}{3} -\frac{2x}{x-1} =x](https://tex.z-dn.net/?f=%5Cfrac%7B3x-1%7D%7B3%7D%20-%5Cfrac%7B2x%7D%7Bx-1%7D%20%3Dx)
![\frac{(3x-1)(x-1)}{3x-3} -\frac{2x(3)}{3x-3} =x](https://tex.z-dn.net/?f=%5Cfrac%7B%283x-1%29%28x-1%29%7D%7B3x-3%7D%20-%5Cfrac%7B2x%283%29%7D%7B3x-3%7D%20%3Dx)
![\frac{3x^2-4x+1}{3x-3} -\frac{6x}{3x-3} =x](https://tex.z-dn.net/?f=%5Cfrac%7B3x%5E2-4x%2B1%7D%7B3x-3%7D%20-%5Cfrac%7B6x%7D%7B3x-3%7D%20%3Dx)
![\frac{3x^2-10x+1}{3x-3} =x](https://tex.z-dn.net/?f=%5Cfrac%7B3x%5E2-10x%2B1%7D%7B3x-3%7D%20%3Dx)
![\frac{3x^2-10x+1}{3x-3} =\frac{x(3x-3)}{3x-3}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%5E2-10x%2B1%7D%7B3x-3%7D%20%3D%5Cfrac%7Bx%283x-3%29%7D%7B3x-3%7D)
![\frac{3x^2-10x+1}{3x-3} =\frac{3x^2-3x}{3x-3}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%5E2-10x%2B1%7D%7B3x-3%7D%20%3D%5Cfrac%7B3x%5E2-3x%7D%7B3x-3%7D)
![3x^2-10x+1=3x^2-3x](https://tex.z-dn.net/?f=3x%5E2-10x%2B1%3D3x%5E2-3x)
![-10x+1=-3x](https://tex.z-dn.net/?f=-10x%2B1%3D-3x)
![-7x=1](https://tex.z-dn.net/?f=-7x%3D1)
![x=-1/7](https://tex.z-dn.net/?f=x%3D-1%2F7)
Rational: Any number that can be expressed as a fraction (or a ratio.)
Irrational: Not rational, any number that can't be written down as a fraction. Some examples include
![\pi (3.1415926...)](https://tex.z-dn.net/?f=%20%5Cpi%20%283.1415926...%29)
,
![\sqrt{2}](https://tex.z-dn.net/?f=%20%5Csqrt%7B2%7D%20)
, and so on.